The effect of therapeutic listening on anxiety and fear among surgical patients: randomized controlled trial - Ana Cláudia Mesquita Garcia; Talita Prado Simão-Miranda; Ana Maria Pimenta Carvalho; Paula Condé Lamparelli Elias; Maria da Graça Pereira; Emilia Campos de Carvalho (Universidade de São Paulo, 2018)
ABSTRACT Objective: To investigate the effect of therapeutic listening on state anxiety and surgical fears in preoperative colorectal cancer patients. Method: A randomized controlled trial with 50 patients randomly allocated in the intervention group (therapeutic listening) (n = 25) or in the control group (n = 25). The study evaluated the changes in the variables state anxiety, surgical fears and physiological variables (salivary alpha-amylase, salivary cortisol, heart rate, respiratory rate and blood pressure). Results: In the comparison of the variables in the control and intervention groups in pre- and post-intervention, differences between the two periods for the variables cortisol (p=0.043), heart rate (p=0.034) and surgical fears (p=0.030) were found in the control group, which presented reduction in the values of these variables. Conclusion: There was no reduction in the levels of the variables state anxiety and surgical fears resulting from the therapeutic listening intervention, either through the physiological or psychological indicators. However, the contact with the researcher during data collection, without stimulus to reflect on the situation, may have generated the results of the control group. Clinical Trial Registration: NCT02455128.